MHD FLOW OF A SECOND ORDER/GRADE FLUID DUE TO NON-COAXIAL ROTATION OF A POROUS DISK AND THE FLUID AT INFINITY - Ersoy, H. Volkan (ASSOC SCI RES, 2010)
The magnetohydrodynamic (MHD) flow of an electrically conducting second order/grade fluid past a porous disk is studied when the disk and the fluid at infinity rotate with the same angular velocity about non-coincident axes. It is found that the existence of solutions is in connection with the sign of the material modulus alpha(1) for both suction and blowing cases. The effects of all the parameters on the flow are carefully examined.
Keywords: fluid rotating at infinity; non-coaxial rotation; second order/grade fluid; magnetohydrodynamics; NON-TORSIONAL OSCILLATIONS; OLDROYD-B FLUID; UNSTEADY-FLOW; HEAT-TRANSFER; MAGNETOHYDRODYNAMIC FLOW; ECCENTRIC ROTATIONS; VISCOUS-FLUID; BURGERS FLUID; HALL CURRENT; PULL; Mathematics